PFAS in Maine: A Case Study in Environmental Governance - Heard, Mya (Maine Policy Review, 2025)
This research describes environmental health governance in response to per- and polyfluoroalkyl substances (PFAS) contamination in Maine. PFAS are a class of 14,700 human-made chemicals that are persistent, ubiquitous, and mobile in the environment, exposure to which is associated with adverse health outcomes. Governance actions that address PFAS contamination are complex, existing between scales of governance, types of governance actions, and across stakeholder groups. Through legislative history research and interviews with stakeholders, I describe Maine’s national leadership in widespread testing, broad regulation, and advocacy on farmland contamination.
Keywords: per- and polyfluoroalkyl substances; PFAS; governance; environmental health